ANALYSIS OF THE VALIDITY OF SALE AND PURCHASE TRANSACTIONS WITH CASH ON DELIVERY SYSTEM ACCORDING TO SHARIA ECONOMIC LAW - Rahmatillah, Putri (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This article aims to analyze the validity of buying and selling transactions with the Cash on Delivery (COD) system according to the perspective of khiyar 'aib. The research method uses qualitative research, which is a type of juridical approach where data is obtained from primary materials in the form of laws and fiqh books. The results of this study conclude that one of the risks in buying and selling transactions with the COD system is the incompatibility of the goods delivered or the goods are damaged. Therefore, the importance of khiyar rights in buying and selling transactions, especially khiyar 'aib. According to the review of muamalah fiqh, it can be concluded that the sale and purchase transaction with the COD system is valid because it has fulfilled the pillars and conditions of sale and purchase and with the enactment of khiyar in the transaction. With the existence of khiyar 'aib in buying and selling transactions, it can minimize the occurrence of losses to one of the parties.